Family functioning, social impairment, and symptoms among adolescents with bipolar disorder. - Keenan-Miller, D; Peris, T; Axelson, D; Kowatch, R; Miklowitz, D (2012)
OBJECTIVE: Impaired social functioning is common among youth with bipolar disorder (BD), emerges in multiple settings, and persists over time. However, little is known about factors associated with poor peer and family functioning in the early-onset form of BD. Using a sample of adolescents with BD I or II, we examined which symptoms of BD, including nonspecific symptoms such as inattention, aggression, and anxiety/depression, were associated with family functioning (adaptability, cohesion, and conflict) and peer relationship quality. METHOD: Adolescents (N = 115; 46% male) with BD I and II and their parents were evaluated before participation in a multi-site randomized controlled trial. Adolescents had experienced an episode of depression, mania, or hypomania within the previous 3 months and were not in full remission. Adolescents' problem behaviors were assessed using the parent-rated Child Behavior Checklist (CBCL). Family functioning was assessed via child- and parent-report questionnaires. RESULTS: Depressive symptoms were associated with lower child-ratings of family functioning. Contrary to hypotheses, moderate mania was associated with better parent-reported family conflict, adaptability, and cohesion. Aggression was associated with poorer family functioning across reporters and measures, even when controlling for the effects of depression, mania, and inattention. None of these symptom clusters were associated with peer functioning. CONCLUSIONS: Aggression was the strongest correlate of family functioning in pediatric BD in this cross-sectional study. Findings speak to the potential value of addressing aggression and family dysfunction in the treatment of youth with BD. Clinical trial registration information-Effectiveness of Family-Focused Treatment Plus Pharmacotherapy for Bipolar Disorder in Adolescents; http://clinicaltrials.gov/; NCT00332098.